Fixation of K allele in K232A polymorphism of DGAT1 gene in Sahiwal and Hariana cattle - Sharma, Anita; Tiwari, Madhu; Singh, Satyendra Pal; Sharma, Deepak; Sumit Kumar,; Pandey, Vijay (Journal of Livestock Biodiversity, 2025)
Diacylglycerol O-acyltransferase 1 (DGAT1) is one of the key enzymes in controlling the rate of triglyceride synthesis in adipocytes, it has been studied as a candidate for association with the milk fat content in cattle. In the present investigation, K232A in polymorphism in exon 8 region of DGAT1 gene has been studied using EaeI/PCR-RFLP assay in Sahiwal and Hariana cattle breeds. The restriction digestion of the 491 bp PCR product showed the presence of KK genotype with a genotypic frequency of 1.0. The KA and AA genotypes were not observed in the screened samples. The allelic frequency of DGAT1 K allele was calculated as 1.0 and that of DGAT1 A allele was zero. The present study revealed monomorphic nature of DGAT1 gene in the screened samples of Sahiwal and Hariana breed.